French from Here, is it French? The Construction of Normativity Judgements in Peripheral European Francophone Communities (Gragoatá, 2021)
This article deals with the diatopic variation of French in its relation to normative discourse, more specifically French as practised in Belgium, exemplified here by the fields of lexicon and syntax. It describes the purist discourse of the last century which is evolving towards a modification of the normative hierarchy, an emancipation from linguistic hegemony, both in the scientific world and in the representations of the speakers. It also leads to a valuable questioning of the identity of the actors responsible for the construction of normative judgements.